Allograft Inflammatory Factor-1 Governs Hematopoietic Stem Cell Differentiation Into cDC1 and Monocyte-Derived Dendritic Cells Through IRF8 and RelB in vitro - Elizondo, Diana M.; Brandy, Nailah Z. D.; da Silva, Ricardo L. L.; Haddock, Naomi L.; Kacsinta, Apollo D.; de Moura, Tatiana R.; Lipscomb, Michael W. (Frontiers in Immunology, 2019)
The multistep differentiation process from hematopoietic stem cells through common myeloid progenitors into committed dendritic cell (DC) subsets remains to be fully addressed. These studies now show that Allograft Inflammatory Factor-1 (AIF1) is required for differentiation of classical DC type 1 (cDC1) subsets and monocyte-derived DC (Mo-DC). Phenotypic studies found that AIF1 expression increased in committed subsets differentiating from common myeloid progenitors (CMP). However, silencing AIF1 expression in hematopoietic stem progenitors restrained the capacity to differentiate into Mo-DC and cDC1 cell subsets under GM-CSF or Flt3-L stimuli conditions, respectively. This was further marked by restrained expression of IRF8, which is critical for development of Mo-DC and cDC1 subsets. As a result, absence of AIF1 restrained the cells at the Lin-CD117+FcγR-CD34+ CMP stage. Further biochemical studies revealed that abrogating AIF1 resulted in inhibition of the NFκB family member RelB expression and p38 MAPK phosphorylation during differentiation of Mo-DC. Lastly, protein binding studies identified that AIF1 interacts with protein kinase C (PKC) to influence downstream signaling pathways. Taken together, this is the first report showing a novel role of AIF1 as a calcium-responsive scaffold protein that supports IRF8 expression and interacts with PKC to drive NFκB-related RelB for successfully differentiating hematopoietic progenitor cells into cDC and Mo-DC subsets under Flt3-L and GM-CSF stimuli, respectively.